Anti-ulcerogenic effect of methanolic extract of Elaeagnus conferta Roxb. seeds in Wistar rats. (15th July 2021) - Gupta, Mukta; Gulati, Monica; Kapoor, Bhupinder; Kumar, Bimlesh; Kumar, Rakesh; Kumar, Rajan; Khurana, Navneet; Gupta, Reena; Singh, Naresh
Abstract: Ethnopharmacological relevance: Elaeagnus conferta Roxb . (Elaeagnaceae) is a subtropical shrub mainly native to India, Vietnam, Malaysia and South China, whose various parts are used for treatment of diabetes, gastric ulcers, pain, oxidative stress and pulmonary disorders. Though the other parts of the plant have been reported for their ethnic use i.e. fruits as astringent locally and for cancer systemically, leaves for body pain and flowers for pain in chest and the seeds are mentioned as edible, there is no report per se on the medicinal use of seeds. Based on the fact that seeds of closely resembling species i.e. Elaeagnus rhamnoides has demonstrated significant anti-gastroulcerative property, the probability of the seeds of E. conferta possessing similar activity seemed quite significant. Aim of the study: Phytochemical investigation and assessment of pharmacological mechanism(s) involved in anti-ulcer effect of methanolic extract of the seeds of E. conferta . Materials and methods: Bioactive phytoconstituents were isolated by column chromatography. These were identified by spectroscopic techniques including infrared (IR) spectroscopy, nuclear magnetic resonance (NMR) and mass spectrometry. Methanolic extract (MEC) of the seeds was prepared by cold maceration and its anti-ulcerogenic potential was evaluated using indomethacin (50 mg/kg) and water immersion stress models in male rats. The animals were pre-treated with different doses of MEC (400 and 800 mg/kg) and the therapeutic effect was compared with standard drug i.e. ranitidine (RANT; 50 mg/kg). The ameliorative effects of MEC were investigated on gastric juice pH, total acidity, free acidity and ulcer index. The assays of malionaldehyde (MDA), catalase (CAT), superoxide dismutase (SOD), glutathione (GSH) and pro-inflammatory cytokines i.e. interleukin-6 (IL-6) and tumor necrosis factor-alpha (TNF-α) were carried out to find out the possible mechanism(s) of protection. Further, histopathological changes were also studied. Results: Chromatography studies and further confirmation by spectroscopic techniques revealed the presence of four different compounds in MEC i.e oleic acid (1), stearic acid (2), ascorbic acid (3) and quercetin (4). MEC exhibited anti-ulcerogenic effect in dose dependent manner which may be attributed to suppression of pro-inflammatory cytokines (IL-6, TNF-α) and MDA (112.7%), and up-regulation of protective factors such as CAT (90.48%), SOD (92.77%) and GSH (90.01%). Ulcer inhibition, reduction in total and free acidity and increase in gastric juice pH were observed in MEC treated rats as compared to disease control animals. Histopathological findings confirmed decreased cell infiltration, less epithelial cell damage and regeneration of gastric mucosa in dose dependent manner. Conclusions: The anti-ulcer effect of MEC may be attributed to its ability to scavenge free radicals and anti-inflammatory property via suppression of TNF-α and IL-6, thus offers a complete and holistic approach for management of peptic ulcer. Graphical abstract: Image 1 Highlights: Methanolic extract of Elaeagnus conferta (MEC) suppresses ulcer formation in Wistar rats by altering biochemical parameters. Gastroprotective effect of MEC is attributed to increase in gastric juice pH, thereby neutralizing gastric acidity. Structure elucidation of isolated compounds confirmed the presence of oleic acid, stearic acid, ascorbic acid and quercetin. MEC suppresses ulceration by down-regulating inflammatory mediators i.e. TNF-α and IL-6. Histopathological findings confirm a decrease in cell infiltration as well as in epithelial cell damage.